A Crop Wild Relative Inventory for Mexico. Issue 3 (1st May 2018) - Contreras‐Toledo, Aremi R.; Cortés‐Cruz, Moisés A.; Costich, Denise; de Lourdes Rico‐Arce, María; Brehm, Joana Magos; Maxted, Nigel
Abstract : Crop wild relatives (CWR) are valuable sources of variation for the genetic improvement of crops. Mexico is an important center of diversity of crops and CWR. However, this diversity is threatened by climate change, habitat degradation, increasing human population, among other factors. Given the large number of CWR, the creation of a CWR inventory is the starting point for the development of a national CWR conservation strategy. The process for the preparation of a national CWR inventory for Mexico consisted of (i) producing a list of national crop species, (ii) matching the crop genera with the list of national flora to produce a CWR checklist, and (iii) prioritizing the CWR checklist according to a series of selection criteria and using a ranking system. The selection criteria included the economic value of the related crop, the potential for crop improvement, food intake, threat status, geographical distribution, and crop use. Applying these criteria, 310 prioritized CWR taxa were selected ( 2% of the national CWR diversity), integrating the national CWR inventory. They are mostly related to food crops of national but also global importance, such as maize ( Zea mays L.), common bean ( Phaseolus vulgaris L.), chili pepper ( Capsicum annuum L.), squash ( Cucurbita spp.), potato ( Solanum tuberosum L.), cassava ( Manihot esculenta Crantz), and sweet potato [ Ipomoea batatas (L.) Lam.]. Approximately 31% of the taxa are endemic to Mexico. The inventory will help to develop in situ and ex situ conservation plans as part of a national CWR conservation strategy.